2006
DOI: 10.1002/chin.200624212
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of FR901464: Second Generation.

Abstract: Antibiotics U 1200Total Synthesis of FR901464: Second Generation. -The title compound (I) is a potent cell cycle inhibitor. -(MOTOYOSHI, H.; HORIGOME, M.; WATANABE, H.; KITAHARA*, T.; Tetrahedron 62 (2006) 7, 1378-1389; Dep. Appl. Biol. Chem., Grad. Sch. Agric. Life Sci., Univ. Tokyo, Bunkyo, Tokyo 113, Japan; Eng.) -Jannicke 24-212

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…6 For comparison, the literature contains only one report of an active carbamate PD analogue (2), which is 4-fold less active than pladienolide B. 4 It is noted that despite several very high quality total syntheses, 9,13,14,20,22 the complexity of 1 has hindered development of extensive SAR data, and there have been no reports on the activity of corresponding 1 reference compounds to compare to most of the analogues in Scheme 1. For example, there are no reports on the synthesis, or bioactivity, of carbamate analogues of 1 to directly compare to carbamates 7-10.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 For comparison, the literature contains only one report of an active carbamate PD analogue (2), which is 4-fold less active than pladienolide B. 4 It is noted that despite several very high quality total syntheses, 9,13,14,20,22 the complexity of 1 has hindered development of extensive SAR data, and there have been no reports on the activity of corresponding 1 reference compounds to compare to most of the analogues in Scheme 1. For example, there are no reports on the synthesis, or bioactivity, of carbamate analogues of 1 to directly compare to carbamates 7-10.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work identified some of the structural requirements for activity in 1 and PD analogues, either by modification of the natural products, 4 or by the total synthesis of some modified compounds (Figure 2). 3,10,12,13 Prior studies have shown the orientation of the acetyl group and the presence of the epoxide to be important in conferring activity to 1 analogues 10,13 and that the glycosidic hydroxyl group can be replaced by an alkoxy 14 or a methyl group 9 to give more stable compounds, or as in the latter case more stable and more active compounds 9 (Figure 2). Active analogues of PD also contain functionality similar to that found in 1, 4,5 though less structure-activity information has been reported on these more recently discovered compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound was converted to the corresponding 2-thiobenzthioazole derivative 11 using Mitsunobu conditions17 and subsequently oxidized to the corresponding 2-sulfonylbenzothioazole derivative 12 10. Removal of the BOC group in 12 and coupling of the optically pure (S,Z)-4-(dimethyl- t -butylsilyloxy)pent-2-enoic acid (prepared according to the known procedure)18 gave the desired functionalized amide 13 in excellent overall yield.…”
mentioning
confidence: 99%
“…2663 and has been shown to inhibit tumour growth in various xenograft models (Nakajima et al, 1996; Nakajima et al, 1996; Nakajima, Sato et al, 1997). FR901464 has been the subject of several successful total synthesis efforts (Thompson et al, 2001; Motoyoshi, et al, 2006; Albert et al, 2007) including the establishment of some structure-activity relationships (SAR) based on the synthesis of new analogs (Thompson et al, 2001; Motoyoshi et al, 2004; Albert et al, 2007; Osman et al, 2011). Most notable among these latter studies was the report of the highly active analogue (meayamycin) by the Koide group (Albert et al, 2007) and their recent very substantial expansion of the SAR work in this area (Osman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%